Throat Colonization of Neonatal Nursery Staff by Ureaplasma urealyticum: an Infection Control or Occupational Health Consideration? - Joanne E Embree; Michelle Alfa; Joy Lertzman; Gloria Gray; Carlos Fajardo; Annalee Yassi (Canadian Journal of Infectious Diseases)
Very low birth weight infants often have protracted respiratory tract colonization with Ureaplasma urealyticum. To determine whether prolonged contact with very low birth weight infants resulted in higher rates of upper respiratory tract colonization with this organism for caregivers, throat swabs for U urealyticum culture were obtained from medical, nursing and other support staff working in the neonatal intensive care and level II nurseries at the Health Sciences Centre and the St Boniface Hospital in Winnipeg, Manitoba. Throat colonization by U urealyticum was demonstrated in 7.3% (95% ci 0 to 15.6%) of 41 nurses working in the intensive care nurseries but in none of the 48 nurses working in other locations or the 66 other individuals tested (P=0.02). However, throat colonization was not significantly higher among the neonatal intensive care nurses than among the women delivering at one of the study institutions. Close contact with very low birth weight infants appears to constitute a minimal risk for increased throat colonization with U urealyticum among hospital staff members.